Neural representation of geoinformation in the human brain: affected by abstraction levels and spatial scales - Tianyu Yang; Bo Zhao; Song Gao; Weihua Dong (Annals of GIS)
The rapid development of cartographical methods has led to cognitive differences in the user experience, presenting a new challenge to microscale research on geoinformation. Prior studies have been constrained by methodologies, and how the human brain represents geoinformation with different levels of abstraction across geographic scales remains unclear. In this study, we conducted a cognitive experiment using functional magnetic resonance imaging with thirteen participants to explore the neural representations of geoinformation abstraction levels and spatial scales. Univariate analysis was utilized to examine the task-state brain imaging representations, and representational similarity analysis was employed to quantify the correlation between two variables and brain signals. We found that the increase in the geoinformation abstraction level decreases the activity of working memory processing, and 3D image induces users to organize geoinformation using egocentric spatial references. Extremely high or low levels of abstraction can hinder effective visual attention allocation. To the best of our knowledge, this is the first report on the neural representation of geoinformation’s abstraction levels and spatial scales, offering new neuroimaging evidence for the theoretical framework of cartography and providing an empirical spatial cognition foundation for future cartographic design.